Evaluating the Side Effects of Treatment for Preterm Labor in a Center that Uses “High-Dose” Magnesium Sulfate - Wilson, Matthew S.; Ingersoll, Melissa; Meschter, Erin; Bodea-Braescu, Ana V.; Edwards, Rodney K. (American Journal of Perinatology, 2014)
Objective To evaluate the tolerability and safety of intravenous magnesium sulfate use for tocolysis in a center that uses a “high-dose” regimen.Study Design We conducted a retrospective cohort study of patients treated with magnesium sulfate for preterm labor from December 2006 to June 2010. Data were abstracted from review of individual patient electronic medical records.Results The cohort consisted of 456 women. Of these, 417 (91.4%) experienced side effects. Severe side effects (pulmonary edema, respiratory arrest, intensive care unit transfer, cardiac arrest, or death) occurred in 24 (5.3%) cases, all but one due to pulmonary edema. No cases of respiratory arrest, cardiac arrest, or death occurred. Those with severe side effects were less likely to have a singleton and more likely to have a higher order multifetal gestation (p < 0.001), received more magnesium, and more often were given multiple concurrent tocolytics (p = 0.04).Conclusion “High-dose” magnesium tocolysis results in side effects for 9 of every 10 patients treated, and severe side effects occur in 1 of every 20 patients. When used for tocolysis, magnesium should be used as a single agent, for less than 48 hours, and with great caution in multifetal gestations.
Keywords: High-dose magnesium side effects